2013
DOI: 10.1212/wnl.0b013e318294b434
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage association study and meta-analysis of mitochondrial DNA variants in Parkinson disease

Abstract: Objectives: Previous associations between mitochondrial DNA (mtDNA) and idiopathic Parkinson disease (PD) have been inconsistent and contradictory. Our aim was to resolve these inconsistencies and determine whether mtDNA has a significant role in the risk of developing PD.Methods: Two-stage genetic association study of 138 common mtDNA variants in 3,074 PD cases and 5,659 ethnically matched controls followed by meta-analysis of 6,140 PD cases and 13,280 controls.Results: In the association study, m.2158T.C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 30 publications
8
92
0
3
Order By: Relevance
“…At the other extreme, common population polymorphisms have a small effect on the risk of developing common human diseases. The most compelling case is for Parkinson disease, and the results of several large studies implicate common mtDNA variants in the pathogenesis of this disease 106 . The same variants might also contribute to the risk of developing several human diseases that share common mitochondrial mechanisms 12 .…”
Section: Box 2 | the Range Of Mtdna Variation And Its Influence On Humentioning
confidence: 99%
“…At the other extreme, common population polymorphisms have a small effect on the risk of developing common human diseases. The most compelling case is for Parkinson disease, and the results of several large studies implicate common mtDNA variants in the pathogenesis of this disease 106 . The same variants might also contribute to the risk of developing several human diseases that share common mitochondrial mechanisms 12 .…”
Section: Box 2 | the Range Of Mtdna Variation And Its Influence On Humentioning
confidence: 99%
“…Smaller studies have reported a contradictory increase in PD risk with haplogroup J [ 96 ], but sample number and genetic heterogeneity, critically misunderstood in the highly mutable mtDNA [ 97 ], may account for this disparity. More recently, a much larger study and meta-analysis confi rmed the role of haplogroup J/K in reducing the risk of PD [ 98 ], an effect which was replicated in a follow-up study later [ 99 ]. A meta-analysis of all available mtDNA-PD data was able to identify that the phylogenetically linked H/V haplogroups increased the risk of PD [ 99 ].…”
Section: Parkinson's Diseasementioning
confidence: 89%
“…Кроме того, увели-чение экспрессии гена паркина свидетельствует о его влиянии на нейропротекторную функцию, регуляцию проявлений оксидативного стресса и митохондриаль-ного биогенеза [18][19][20].…”
Section: N¹ 6 (92) 2017unclassified